1995
DOI: 10.1055/s-2007-1015974
|View full text |Cite
|
Sign up to set email alerts
|

Quantifizierung der Lymphknotenperfusion mittels farbkodierter Duplexsonographie

Abstract: Clinically known subjective signs of malignancy (increased size, low echogenicity, alterations of the perfusion) can be analysed quantitatively to differentiate benign from malignant lymphadenopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…The RI and PI could be determined in 2 examinations before and after application of the signal enhancer, and in 4 examinations quantitative variables could be determined only after application of the signal enhancer. According to Tschammler et al, 13 pathologic arterial Doppler spectra in metastatic lymph node vessels were quantified with an RI of 0.9 or higher or a PI of 1.8 or higher. Before application of the contrast enhancer, measurement of the PI and RI in native CDS did not help to determine metastatic disease, which was found after histopathologic examination after excision of the lesions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RI and PI could be determined in 2 examinations before and after application of the signal enhancer, and in 4 examinations quantitative variables could be determined only after application of the signal enhancer. According to Tschammler et al, 13 pathologic arterial Doppler spectra in metastatic lymph node vessels were quantified with an RI of 0.9 or higher or a PI of 1.8 or higher. Before application of the contrast enhancer, measurement of the PI and RI in native CDS did not help to determine metastatic disease, which was found after histopathologic examination after excision of the lesions.…”
Section: Methodsmentioning
confidence: 99%
“…In the past, different groups tried to establish quantitative thresholds for defining vascularity of malignant respectively benign lymph nodes. 13,[20][21][22] Choi et al 21 defined a PI more than 1.5 and an RI more than 1.0 to be characteristic for malignancy, whereas Steinkamp et al 22 postulated 1.6 and 0.8 as thresholds for PI and RI, respectively. The most often used classification is the one of Tschammler et al, 13 who found lymph nodes with a PI of 1.8 or more and an RI of 0.9 or more to be suggestive of malignancy.…”
Section: Commentmentioning
confidence: 99%
“…24 To obtain more objective criteria, different groups have tried to establish quantitative thresholds for defining vascularity of malignant and benign lymph nodes. The most often used classification is that of Tschammler and colleagues, 25 who found lymph nodes with a pulsatility index of 1.8 or more and a resistive index of 0.9 or more to be suggestive of malignancy. In our own patients with melanoma, the pulsatility index and resistive index values were disappointing in their ability to separate malignant from benign lymph nodes 21 ; Moehrle and coworkers 26 have reported the same problem.…”
Section: Native and Signal-enhanced Cdsmentioning
confidence: 99%
“…The threshold value or colour gain defines the minimum amplitude of Doppler signals which will be colour encoded; therefore, the relation between the threshold and the detection of intranodal flow signals was to be expected. This parameter is used most frequently [3,4,11,12,14,17] to optimise individually colour saturation, but there is no information on the appropriate range of settings. The wall filter is a high-pass filter which suppresses low-frequency Doppler signals originating principally from arterial pulsation, respiration and involuntary movements.…”
Section: Intranodal Flow Detectionmentioning
confidence: 99%